Effectiveness of home-based upper limb rehabilitation in stroke survivors: A systematic review and meta-analysis - Toh, Sharon Fong Mei; Chia, Pei Fen; Fong, Kenneth N. K. (Frontiers in Neurology, 2022)
Background: Home-based training is an alternative option to provide intensive rehabilitation without costly supervised therapy. Though several studies support the effectiveness of home-based rehabilitation in improving hemiparetic upper limb function in stroke survivors, a collective evaluation of the evidence remains scarce. Objectives: This study aims to determine the effects of home-based upper limb rehabilitation for hemiparetic upper limb recovery in stroke survivors. Methods: The databases of the Cochrane Library, MEDLINE, CINAHL, and Web of Science were systematically searched from January 2000 to September 2020. Only randomised, controlled, and cross-over trials that evaluated the effects of home-based upper limb interventions were selected. The Pedro scale was used to assess the methodological quality of the studies. A meta-analysis of the upper limb function outcomes was performed by calculating the mean difference/standardised mean difference using a fixed/random effect model. Results: An initial search yielded 1,049 articles. Twenty-six articles were included in the review. The pooled evidence of the meta-analysis showed that home-based upper limb intervention was more effective in improving upper limb function (SMD: 0.28, 95% CI (0.12, 0.44), I2=0%, p<0.001, fixed effect model) than conventional therapy. When comparing two types of home-based interventions, subgroup analysis revealed that home-based technology treatment – electrical stimulation – provided more significant improvement in upper limb function than treatment without the use of technology (SMD: 0.64, 95%CI (0.21, 1.07), I2=0%, p=0.003, random effect model). Conclusion: The beneficial effects of home-based upper limb interventions were superior to conventional therapy in improving function and perceived use of the hemiparetic upper limb in daily activities. Among the home-based interventions, home-based electrical stimulation seemed to provide the most optimal benefits.